2015
DOI: 10.1016/j.pec.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ reports of barriers to expressing concerns during cancer consultations

Abstract: The results of this study can be used to develop strategies to overcome barriers to patients expressing concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 34 publications
5
37
0
9
Order By: Relevance
“…These barriers appeared quite similar to the concerns reported by 236 cancer patients about their regular consultations with their health professionals [1]. Brandes et al [1] reported that patients indicated their primary barriers to discussing their concerns with health professionals related to the health professionals' behaviour (e.g.…”
Section: Physical Activity Promotion Practices and Determinants Of Hementioning
confidence: 63%
See 1 more Smart Citation
“…These barriers appeared quite similar to the concerns reported by 236 cancer patients about their regular consultations with their health professionals [1]. Brandes et al [1] reported that patients indicated their primary barriers to discussing their concerns with health professionals related to the health professionals' behaviour (e.g.…”
Section: Physical Activity Promotion Practices and Determinants Of Hementioning
confidence: 63%
“…Brandes et al [1] reported that patients indicated their primary barriers to discussing their concerns with health professionals related to the health professionals' behaviour (e.g. a lack of empathy, not inviting the patients' to identify their concerns and an inability to provide accurate information) as well as the consultation environment (e.g.…”
Section: Physical Activity Promotion Practices and Determinants Of Hementioning
confidence: 99%
“…o kind of barrier is related to the provider's environment, such as not having enough time to listen to patients' concerns; not paying attention to patients and instead constantly looking at his or her computer screen; and patients being unable to choose a provider. 30 The third kind of barrier affects the patient's attitude and empowerment: for example, patients being afraid they are wasting their provider's time when they express their concerns, patients feeling ashamed when they express their concerns, and patients being afraid that expressing their concerns will damage their relationship with their provider. 30 The provider's paternalistic or patronizing attitude along with a medical-model practice will insult, segmentalize, and reduce the consumer's choice.…”
Section: Resultsmentioning
confidence: 99%
“…21 Brief and hurried interactions with health-care providers are commonly reported by individuals with MS. 29 Individuals with MS have recommended that health professional training can better prepare providers to adequately meet the needs of patients by strengthening listening and communication skills with individuals with disabilities. Brandes et al 30 found three kinds of communication barriers between health-care providers and patients with chronic disease. The first kind of barrier is related to the provider's behavior, such as not responding with empathy when patients express a concern, not explicitly inviting patients to discuss their concerns, and not facilitating interactions where patients feel they are stupid when expressing their concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation